2004
DOI: 10.1177/082585970402000109
|View full text |Cite
|
Sign up to set email alerts
|

Providing Cancer and Palliative Care in Rural Areas: A Review of Patient and Carer Needs

Abstract: Of 72 papers identified, 71 were obtained and 20 were considered to meet the inclusion criteria. One paper could not be traced by library sources, due to incorrect referencing. Of the total of 20, 11 focused on needs of patients or carers; five were surveys of place of death or end-of-life care; and four were reviews of services in specific areas, which included reporting of patient and caregiver needs. The papers identified all originate from the developed world and there were no studies specifically relating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 26 publications
2
29
0
Order By: Relevance
“…This review expands on previous reviews by contrasting the key deficit of reduced availability and skills of primary care professionals with the advantages of rural resilience and community and patient and caregiver support. Unmet PEOLC need was related to lack of local services and reduced access to specialist services.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…This review expands on previous reviews by contrasting the key deficit of reduced availability and skills of primary care professionals with the advantages of rural resilience and community and patient and caregiver support. Unmet PEOLC need was related to lack of local services and reduced access to specialist services.…”
Section: Discussionmentioning
confidence: 89%
“…Previous reviews have not identified specific rural and remote PEOLC needs, but recognised the negative impact of geography and workforce. The positive influence of rurality on human attributes, such as resilience and community connectedness, which in turn influence health outcomes, has also been identified . Specific problems in symptom control and management of emotional issues have been reported in rural studies as well as difficulties in accessing specialist services, such as hospices and bereavement counselling and information .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This socially oriented context of care that invites going beyond 'the call of duty' can be associated with high personal cost [27] and can lead to a sense of isolation and burnout [28]. It has been noted that there is also a high degree of family caregiver burden associated with rural palliative care [29]. So, while rewarding, being present and available is not without risks.…”
Section: Discussionmentioning
confidence: 99%